Incidence of Cytomegalovirus Retinitis in the Era of Highly Active Antiretroviral Therapy - Sugar, Elizabeth A.; Jabs, Douglas A.; Ahuja, Alka; Thorne, Jennifer E.; Danis, Ronald P.; Meinert, Curtis L. (American journal of ophthalmology, 2012)
To estimate the incidence of cytomegalovirus (CMV) retinitis in the era of highly active antiretroviral therapy (HAART) and to characterize the factors associated with increased risk of CMV retinitis. Prospective cohort study. A total of 1600 participants with acquired immunodeficiency syndrome (AIDS) but without CMV retinitis at enrollment who completed at least 1 follow-up visit in the Longitudinal Study of the Ocular Complications of AIDS (LSOCA) were seen every 6 months to obtain disease and treatment history, ophthalmic examination, and laboratory testing. Incidence of CMV retinitis and risk factors for incident CMV retinitis were assessed. The incidence rate of CMV retinitis in individuals with AIDS was 0.36/100 person-years (PY) based upon 29 incident cases during 8134 PY of follow-up. The rate was higher for those with a CD4+ T cell count at the immediately prior visit below 50 cells/μL (3.89/100 PY, P < .01), whereas only 1 individual with a CD4+ T cell count of 50 to 99 cells/μL and 2 individuals with a CD4+ T cell count >100 cells/μL developed CMV retinitis. Having a CD4+ T cell count below 50 cells/μL at the clinical visit prior to CMV retinitis evaluation was the single most important risk factor (HR: 136, 95% CI: 30 to 605, P < .0001) for developing retinitis. Patients with AIDS, especially those with severely compromised immune systems, remain at risk for developing CMV retinitis in the HAART era, although the incidence rate is reduced from that observed in the pre-HAART era.